Investigating mobile graphic-based reminders to support compliance of tuberculosis treatment - Haji, Haji Ali (Department of Computer Science, 2018)
The phenomenon of rapid increment of the mobile phones can be utilized through supporting patients, such as those who have tuberculosis, for treatment adherence. This utilization will enable these patients to directly communicate their needs and requirements or receive health information such as reminder messages from healthcare facilities. However, the current mobile interventions, such as text messaging and speech reminder systems have limited use for people with low literacy levels. To overcome these challenges, this study proposed that the mobile graphic-based reminders be used to support tuberculosis patients to improve compliance with treatment regimens, especially for semi-literate and illiterate patients. A review of the literature and initial investigation study were carried out. The findings from the review were useful in understanding both the current practice of tuberculosis treatment regimens and the patients' needs and requirements. These findings, in addition, were referred in the choices of the components of the mobile graphic-based reminders to be implemented. A visual aid for communication theory was applied to the design and development of graphic-based reminder prototypes. An application prototype was implemented for the Android platform. Experiments were conducted to investigate the effects of an application prototype in supporting tuberculosis treatment. To measure the effect, the recovery rate was measured based on the effect of: (1) the graphic-based reminder group versus the control group; and (2) the graphic-based reminder group versus the speech-based reminder group. Data was collected using application event logs, interviews, field notes and audio recordings. It was found that treatment adherence of patients in the graphic-based group was higher than in the speech-based or in the control groups. It was further noted that the number of reminder responses in the graphic-based group was higher than in the speech-based group. Additionally, it was observed that patients in the graphic-based group responded sooner after receiving reminder messages compared to those in the speech-based group. The qualitative feedback also indicated that most patients not only found graphic-based reminders more useful to supporting their treatment than speech-based reminders and traditional care but believed that the application met their needs. This study provides empirical evidence that graphic-based reminders, designed for and based on patients' needs and requirements, can support the treatment of tuberculosis for patients of all literacy levels.